3D scanning as a powerful tool for the analysis of bird nests. Issue 3 (August 2020) - Simonov, Sergey; Matantseva, Maria
The analysis of bird nest parameters is often constrained by the traditional linear measurements. The shape of every nest is unique, and conventional measurements cannot describe all spatial characteristic of these three-dimensional structures. In this study, we used 3D scanning to obtain three-dimensional images of nests and estimate their parameters and compared the results with the values obtained by the linear measurement-based approach. The 3D scanning-based method involves minimal nest deformation, ensures determination of its volume and shape with higher precision than traditional measurements and, finally, can be applied to different types of nests, including asymmetrical ones.